Management of Competency Certification Assessment by Professional Certification Body of Tengaran Vocational High School Semarang Regency - Aris Abadi; Sutama Sutama; Ahmad Muhibbin (Budapest International Research and Critics University, 2022)
Competency Certification Assessment is a process of assessing students against the fulfillment of the requirements set out in the certification scheme and providing recognition of competence to vocational high school students. Competence is a major part of Vocational High School students because it shows the workability of each individual which includes aspects of knowledge, skills, and work attitudes that are in accordance with the expected standardization. The purpose of this research is to find out: 1) planning of competency certification assessment, 2) competency certification assessment process, 3 follow-up competency certification assessment. The research uses qualitative methods which are used to examine natural objects, where the researcher is the key instrument. Using the type of phenomenology where the researcher's investigation is carried out on a program, event, activity, or process of a group of individuals. Researchers use interviews, observations, and data review of competency certification assessment. Based on the results of the study, it can be concluded that the management of the Competency Certification Assessment by the Professional Certification Body of Tengaran Vocational High School begins with planning and is divided into two types of planning, administrative or document planning, and facilities/infrastructure planning. Furthermore, in the Competency Certification assessment process using cluster installments, where assessment participants will take cluster fractions to get KKNI level II on a scheme that matches their major. The follow-up to the Competency Certification Assessment is the issuance of a certificate, where only the assessment participants who are declared competent will receive a competency certificate, and the last follow-up is the validation of the assessment process. Validation of the assessment pays attention to critical aspects, including the assessment process, methods/tools, evidence collected, and assessment decisions.